2020
DOI: 10.14715/cmb/2019.66.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantification analysis of lactate dehydrogenase and C-reactive protein in evaluation of the severity and prognosis of the acute pancreatitis

Abstract: To evaluate the value of C-reactive protein (CRP) and lactate dehydrogenase (LDH) in assessing the severity and prognosis of acute pancreatitis (AP).A retrospective analysis was performed with the clinical data of 115 AP patients who were delivered to this hospital between December 2012 and December 2017 for treatment, in which there were 76 patients with mild AP (MAP group) and 39 with moderately severe AP (MSAP) and severe AP (SAP) (non-MAP group).Within 24 h after admission, we detected the levels of CRP, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, in this study, we didn’t find any difference in HDL level between the POF and the TOF groups, which could be due to the different etiological characteristics of AP in the general population and APIP. The etiology of AP in the general population is mainly biliary type ( 34 , 35 ), while APIP is mainly HTG type ( 1 ). The changes of lipid metabolism in the latter may be different from that in biliary type AP.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, we didn’t find any difference in HDL level between the POF and the TOF groups, which could be due to the different etiological characteristics of AP in the general population and APIP. The etiology of AP in the general population is mainly biliary type ( 34 , 35 ), while APIP is mainly HTG type ( 1 ). The changes of lipid metabolism in the latter may be different from that in biliary type AP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that LDH may play a role in predicting adverse events. To patients with tumor, such as small cell lung cancer, hepatocellular carcinoma, and acute pancreatitis, elevated LDH represents a bad prognosis [ 15 , 20 , 21 ]. These discoveries confirmed our speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin is the precursor of the hormone calcitonin found in the thyroid C cells and the pulmonary endocrine cells [26]. However, all tissues have the potential to produce procalcitonin [27].During systemic infections, blood PCT levels rapidly increase within 3-6 h, persisting during the in ammatory process, and decrease as the infection starts to subside [28].Reza has reported that serum PCT was a valuable predictor of SAP in the general population [29].Hence, PCT may facilitate the monitoring of progression in AP in general people [29][30][31].…”
Section: Discussionmentioning
confidence: 99%